Maternal child nursing care - Wong, Donna L.; Perry, Shannon E.;Hockenberry, Marilyn J.;Lowdermilk, Deitra Leonard;Wilson, David (Singapore : Mosby Elsevier, 2009)
The text focuses on the care of women during theor reproductive years and on children from newborn through adolescence. The promotion of wellness and the management of common women's health problems and child development are also addressed.
Part I: Maternity nursing -- Part II: Pediatric nursing
Includes index.
Keywords: MATERNAL-CHILD NURSING